Bacterial phylogenetic markers in lake sediments provide direct evidence for historical hemp retting. (1st November 2022) - Rull, Valentí; Sacristán-Soriano, Oriol; Sànchez-Melsió, Alexandre; Borrego, Carles M.; Vegas-Vilarrúbia, Teresa
Abstract: Documenting prehistoric and historical hemp retting for fiber extraction is important in the study of human uses of this iconic plant and its cultural implications. In paleoecology, hemp retting is usually inferred from indirect proxies, notably anomalously high percentages of Cannabis pollen in lake sediments, but some recent studies have also used specific molecular biomarkers (cannabinol, Cannabis DNA) as more straightforward evidence. Here we provide direct evidence of hemp retting by identifying phylogenetic signatures ( 16S rRNA genes) from pectinolytic bacteria actually responsible for the fermentation process that separates the fiber from the stalk, namely Bacillus, Clostridium, Escherichia, Massilia, Methylobacterium, Pseudomonas, Rhizobium and Rhodobacter . These analyses have been performed in the sediments from an Iberian lake previously considered as an important hemp retting site during the last five centuries, on the basis of Cannabis pollen abundances. The good match between biomarker and pollen evidence, in the context of the recent historical development of the hemp industry in Spain, can be useful to interpret paleoecological records from other similar lakes on the way toward a more regional view on the introduction, spreading, uses and associated cultural connotations of Cannabis in the Iberian Peninsula within European and Mediterranean contexts. Highlights: Sedimentary 16S rRNA genes from retting bacteria are direct indicators of hemp retting. Retting trends of the last five centuries match historical developments of hemp industry. Phylogenetic evidence of hemp retting occurs at Cannabis pollen values over 20%.